(untitled) (Journal of Asian Development Studies, 2024)
Teaching practicum is a vital component of pre-service teaching courses. However, researchers have shown concern about the quality of implementation of these courses. Resultantly, students show low-profile abilities in teaching and learning when they join professional service as teachers. The primary purpose of this study was to develop a scale for exploring strategies for effective practicum implementation and, secondly, to ascertain teachers’ perceptions about the effect of these strategies on the effective implementation of teaching practicum in schools. A survey questionnaire was developed and used for data collection. The questionnaire was developed based on a review of the literature and expert judgment. A total of 77 students participated in the study from a private college of teacher education in Peshawar. The students were selected based on a convenient sampling technique. The dimensionality of the scale was checked through exploratory factor analysis. The principal component analysis revealed a 4-factor structure as an essential strategy for the effective implementation of teaching practicum for pre-service teachers. These strategies were clear communication, showing respect, professional behavior and motivation. It is concluded that the scale can be used for measuring the effectiveness of teaching practicum in other contexts. The results of this study may be used for improving the curriculum implementation of teaching practicum in teacher training institutes. This study is significant as it provides firsthand knowledge to the management and administration of teacher education institutions about the essential strategies that can be used to enrich further teaching practicum, a pivotal element of teacher education.